2005
DOI: 10.1538/expanim.54.437
|View full text |Cite
|
Sign up to set email alerts
|

Development of Intestinal Microbiota in Mice and Its Possible Interaction with the Evolution of Luminal IgA in the Intestine

Abstract: The development of the intestinal microbiota and the evolution of the fecal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…Piglets are born with little or no passive immunity, as there is no transfer of antibodies in utero, but they do acquire maternal antibody from colostrum and milk (Westrom et al, 1984). It has been suggested that in mice, the lag time between the decline in IgA levels at weaning and the maturation of mucosal immune system allows an increase in bacterial colonization (Inoue et al, 2005a). We observed detectable levels of fecal IgA in the earliest samples (3-7 day-olds).…”
Section: Discussionmentioning
confidence: 58%
“…Piglets are born with little or no passive immunity, as there is no transfer of antibodies in utero, but they do acquire maternal antibody from colostrum and milk (Westrom et al, 1984). It has been suggested that in mice, the lag time between the decline in IgA levels at weaning and the maturation of mucosal immune system allows an increase in bacterial colonization (Inoue et al, 2005a). We observed detectable levels of fecal IgA in the earliest samples (3-7 day-olds).…”
Section: Discussionmentioning
confidence: 58%
“…However, as the colonization process was equally or more successful in the weaning study, there was no advantage of autoclaving cages and assorted items. Furthermore, diversification of the mouse gut microbiota usually occurs at three weeks of age, likely due to a decrease in maternal immunoglobulin A (IgA) supply when mice stop suckling, making this a proper time point for inoculation with gut microbiota20. Recipients in the adult study had a higher diversity of gut microbiota within the groups than the controls receiving PBS one week after inoculation, suggesting that the recipients colonize on the inoculation given.…”
Section: Discussionmentioning
confidence: 99%
“…Further elucidation of the effect of diet and sex of piglets should be considered. The period characterized by a low intestinal sIgA level is as short as a few days in the case of the rodent model [4,5]. Bacteria colonize intensively in the intestine during this period [4,5].…”
mentioning
confidence: 99%